Federal reserved rights and California's Groundwater Management Act: resolving groundwater rights tensions in California and the western United States. Issue 4 (19th May 2019) - Schulte, Stefanie Viktoria Caroline
ABSTRACT: California introduced its first comprehensive groundwater legislation (the Sustainable Groundwater Management Act) in 2014 to address the overuse of the state's groundwater resources and to establish a pathway for sustainable groundwater use. However, a recent decision by the US Court of Appeals for the Ninth Circuit declaring the existence of federal reserved rights to groundwater could complicate the future implementation of California's new groundwater legislation. This article explores the impact of the case and offers recommendations on how the tensions between the court's decision and the existing legal framework for groundwater management in California could be reduced.